Efektifitas Senam Ergonomi Terhadap Penurunan Tekanan Darah Pada Lansia Di LKS.LU Beringin Kabupaten Gorontalo - Indriyani Rusli Madidi; Rona Febriona; Haslinda Damansyah (Jurnal Rumpun Ilmu Kesehatan, 2023)
.Degenerative diseases in the elderly, if not handled properly, will add to the state’s financial burden, which is not small. This study’s general purpose was to determine ergonomic gymnastics’s effectiveness in lowering blood pressure in the elderly. This research method uses a pre-experiment with a group pre-test and post-test design. The sample in this study amounted to 20 people, using the purposive sampling technique. The results of this study indicate that respondents before being given the intervention had blood pressure in the Stage 1 hypertension category, as many as 12 respondents (60%), and in the Stage 2 hypertension category, as many as eight respondents (40%). After being given the intervention, blood pressure in the Stage 1 hypertension category, as many as two respondents (10%), and pre-hypertension, as many as 18 respondents (90%). The chi-square statistical test showed a p-value = 0.018 (p < 0.05). These results indicate that H0 is rejected Ha is accepted, so it can be concluded that ergonomic exercises effectively reduce blood pressure in the elderly. It is recommended that health center officers socialize with the elderly by providing ergonomic exercises to reduce changes in blood pressure in elderly patients.